Prognostic and predictive value of Ki-67 in triple-negative breast cancer - Wang, Wei (Oncotarget, 2016)
This study was to investigate the prognostic role of Ki-67 in further classification of triple negative breast cancer (TNBC), and to test whether high expression level of Ki67 can predict benefit from carboplatin. From January 2004 to December 2012, 363 patients operated for TNBC were identified through the institutional clinical database. After a median follow-up time of 34 months (5.2–120.0 months), 62 patients (17.1%) had relapses and 33 patients (9.1%) died of breast cancer. In univariate analysis, high Ki-67 index as well as larger tumor size and lymph node involvement was associated with shorter disease-free survival (DFS) and overall survival (OS). In multivariate analysis, high Ki-67 is an independent risk factor for DFS (Risk Ratio, RR: 2.835, 95% confidence interval, 95% CI: 1.586–5.068, P < 0.001) and OS (RR: 3.180, 95% CI: 1.488–6.793, P = 0.003). When analyzing the 3-year DFS by Ki-67 distribution, Subpopulation Treatment Effect Pattern Plot analysis showed a beneficial effect of carboplatin in patients with high Ki-67 index. In conclusion, TNBC is probably a heterogeneous disease with different characteristics and prognosis, and may be further subdivided according to the Ki-67 expression levels. Patients in the high Ki- 67 group seem to benefit more from treatment with carboplatin, but this needs to be further verified.